The effect of filling density on flammability and mechanical properties of 3D-printed carbon fiber-reinforced nylon - Lucie Zárybnická; Jana Machotová; Marek Pagáč; Jozef Rychlý; Anna Vykydalová (Polymer Testing, 2023)
3D printing of reinforced polymeric materials, which provides products of excellent physical and mechanical properties, is at the forefront of interest in the field of additive technologies. To ensure material, time, and financial savings, 3D objects having reduced filling density are frequently prepared. The presented work aims to study the effect of different levels of filling density (18, 42, and 62% using a honeycomb filling pattern) in contrast to 100% solid fill of carbon fiber-reinforced polyamide 6.6 materials processed by Fused Filament Fabrication on their flammability and mechanical properties. Concurrently, the effect of a commercial flame retardant additive concerning the filling density was also evaluated. The flammability and mechanical properties of the 3D printed materials were evaluated according to cone calorimeter measurements, and tensile and bending tests, respectively. It was found that the reduction in the filling density led to a pronounced decrease in mechanical properties (of about 40–50% for tensile and bending stress) and also to the deterioration of flame resistance (of about 50–70% shorter burning time), with no unambiguous correlation with the respective filling density level used. If significant economic savings are preferred, 3D objects designed with low levels of filling density (18 or 42%) are advantageous to be manufactured from nylon stabilized with a flame retardant additive, resulting in acceptable fire-resistant properties.